2016
DOI: 10.1080/10942912.2015.1050595
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Rheological Properties of White-Cheek Shark (Carcharhinus dussumieri) Skin Gelatin

Abstract: Physicochemical and rheological properties of white-cheek shark (WS, Carcharhinus dussumieri) skin gelatin were determined as a function of either an alkaline-acid or an acid pretreatment. With alkaline-acid pretreatment, the purity of WS skin gelatin was increased, with a significant lower extraction yield, a higher retention of high molecular weight components, and Downloaded by [New York University] at 03:31 16 July 2015A c c e p t e d M a n u s c r i p t 2 greater preservation of the triple helical structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…Structural information can help in determining the properties of fish skin gelatin. [4] Several studies have explored the nanostructure of fish gelatin. [3,9,36] However, few studies have used AFM to observe the gelatin extracted by CWB and UWB at different temperatures.…”
Section: Nanostructure Of Fish Gelatin Extracted By Wb and Uwbmentioning
confidence: 99%
See 3 more Smart Citations
“…Structural information can help in determining the properties of fish skin gelatin. [4] Several studies have explored the nanostructure of fish gelatin. [3,9,36] However, few studies have used AFM to observe the gelatin extracted by CWB and UWB at different temperatures.…”
Section: Nanostructure Of Fish Gelatin Extracted By Wb and Uwbmentioning
confidence: 99%
“…Gelatin, a proteinaceous material derived from collagen, is an important biological polymer that has been widely used in food and pharmaceutical industries. [1][2][3][4] However, with the emergence of bovine spongiform encephalopathy and foot-and-mouth disease affecting human health, the safe use of mammalian gelatin has been disputed for many years. [5] Furthermore, pig gelatin is not acceptable in Judaism and Islam because of their religious beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher degree of protein denaturation resulted in higher exposure of the functional groups and subsequently hardness of the MP gels. Tabarestani et al [43] suggested that weakened gel structures seen as lower hardness might be caused by the reduction of the formation of linkages between aggregated helices. Hardness is related directly to the strength of the gel structure under compression.…”
Section: Effects Of Oxidation On Textural Properties and Water Holdinmentioning
confidence: 99%